The big book of classic fantasy : the ultimate collection - VanderMeer, Ann; VanderMeer, Jeff (Vintage Crime/Black Lizard, Vintage Books, 2019)
*Stories by pillars of the genre like the Brothers Grimm, Hans Christian Andersen, Mary Shelley, Christina Rossetti, L. Frank Baum, Robert E. Howard, and J. R. R. Tolkien *Fantastical offerings from literary giants including Edith Wharton, Leo Tolstoy, Willa Cather, Zora Neale Hurston, Vladimir Nabokov, Hermann Hesse, and W.E.B. Du Bois *Rare treasures from Asian, Eastern European, Scandinavian, and Native American traditions *New translations, including fourteen stories never before in English PLUS: *Beautifully Bizarre Creatures! *Strange New Worlds Just Beyond the Garden Path! *Fairy Folk and Their Dark Mischief! *Seriously Be Careful<U+2014>Do Not Trust Those Fairies!